The vortex formation in a horizontal finite cylinder by alternating electric current - Buikis, A. (Mathematical Modelling and Analysis, 2005)
We have investigated and calculated the distribution of electromagnetic fields and forces induced by a three‐ phase axially‐symmetric system of electric current with six electrodes in a cylinder of a finite length [1, 3]. In this paper the alternating current is fed to each of nine discrete circular conductors‐electrodes, which are placed on the internal wall of the cylinder. This new mathematical model describes a real device [7], which transforms electric energy into heat. The viscous incompressible flow of weakly electroconductive liquid‐electrolyte is obtained by the finite‐difference method, using the monotonous vector finite difference schemes. The average axially‐symmetric motion of electrolyte and vortex distribution in a cylinder has been considered. The dependence of electromagnetic forces and velocity distribution at the inlet of the cylinder is investigated in the case of:• the vortex formation from the Lorentz force inside the cylinder by the electrode;• the vortex‐breakdown from the swirl velocity at the inlet of the cylinder.Sūkurio sudarymas horizontaliame baigtiniame cilindre kintama elektros sroveStraipsnyje yra nagrinėjamas skysto elektrolito judėjimas baigtiniame cilindre, veikiamas kintančio elektromagnetinio lauko. Panaudojant savo anksčiau sukurtą metodą suvidurkintų laike elektromagnetinių jėgų reikšmių gavimui, autoriai formuluoja stacionarų Navier‐Stokso uždavinį klampiam nespūdžiam elektrolito tekėjimui aprašyti. Sukurto matematinio modelio skaitiniam sprendimui yra pasiūloma originali monotoninė baigtinių skirtumų schema. Yra pateikiami skaitinių eksperimentų rezultatai su 9 žiediniais laidininkais‐elektrolitais, tolygiai paskirstytais vidiniame cilindro paviršiuje. Autoriai analizuoja gaunamus cilindre srautus priklausomai nuo elektromagnetinių jėgų pasiskirstymo (skirtingos elektrodu pajungimo schemos) ir sūkurinio greičio cilindro įėjime. Labiausiai autorius domina sąlygos, kada cilindro viduje susidaro sūkuriai.First Published Online: 14 Oct 2010